Kompetensi Kepribadian Guru Dalam Perpektif Muhammadiyah - Reni Sasmita; Mhd. Lailan Arqam (Universitas Islam Sultan Agung, 2022)
The problems that occur in Muhammadiyah teachers are their behavior that is less moral, has a bad personality, and also weak mastery of religious norms. So this will have an impact on the professionalism of a teacher. What happened to teachers at Muhammadiyah schools was due to the weak mastery and understanding of the personality competencies that a teacher must-have. The method used in this research is the library method, which is a research method whose data sources come from books, scientific articles, and documents related to the topic of the problem. The conclusion of this study is that not only is the source of knowledge, but a teacher is also a person who is nurtured and imitated by his students. Teachers at Muhammadiyah schools are teachers who not only master the knowledge they teach but also have to master and understand Muhammadiyah and also have piety to God and are able to be role models for their students. The Personality Competence of Muhammadiyah teachers as contained in the Guidelines for the Islamic Life of Muhammadiyah Citizens (PHIWM) which is also in accordance with Law no. 14 of 2005 concerning teachers and lecturers are compassionate, Uswatun Hashanah, noble character (pious personality), Islamic work ethic, and also Istiqomah Commitment. The personality of Muhammadiyah teachers must be reflected in their daily lives, both in the school, family, and community and within the scope of the Muhammadiyah organization.